2008
DOI: 10.1124/dmd.107.019448
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Multidrug Transporter Proteins ABCB1 and ABCC2 in the Diaplacental Transport of Talinolol in the Term Human Placenta

Abstract: ABSTRACT:Placental syncytiotrophoblasts are known to express the efflux transporter proteins P-glycoprotein (ABCB1) and multidrug resistance-associated protein 2 (ABCC2), which are supposed to be a functional part of the human placental barrier. With advancing gestational age, expression of ABCB1 decreases progressively, whereas ABCC2 is more expressed. To evaluate to which extent they contribute to placental barrier function at term, permeability of talinolol, a substrate of both carriers, was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…May et al . reported that the materno-fetal transfer of talinolol in the human placental perfusion model was sensitive to probenecid, consistent with MRP2 involvement in the transplacental transfer of this substrate (164). Bridges et al examined the disposition of the mercuric ions in the placental and fetal tissues.…”
Section: Abc Transporters In the Placentamentioning
confidence: 57%
“…May et al . reported that the materno-fetal transfer of talinolol in the human placental perfusion model was sensitive to probenecid, consistent with MRP2 involvement in the transplacental transfer of this substrate (164). Bridges et al examined the disposition of the mercuric ions in the placental and fetal tissues.…”
Section: Abc Transporters In the Placentamentioning
confidence: 57%
“…Placenta Perfusion-Immediately after delivery, the fetal and maternal sides of three placentas were perfused as described recently (30). The flow rate was 12 ml/min in the maternal circuit and 4 ml/min in the fetal circuit with an arterial pressure between 25 and 40 mm Hg.…”
Section: Methodsmentioning
confidence: 99%
“…Internalization of OATP2B1 in a Placenta Perfusion ModelTo answer the question whether PKC-mediated OATP2B1 internalization also plays a role in the biological system, we performed human placenta perfusion studies, a model system that is often used to investigate feto-maternal drug transport and vice versa (30). Using this system we could demonstrate an internalization of OATP2B1 following PMA perfusion (Fig.…”
Section: Establishment Of a Gfp-oatp2b1-expressing Cell Line And Timementioning
confidence: 99%
“…In addition to this, it can transport a number of sulfate, glucuronide, and glutathione conjugates [96]. Xenobiotics that are transported by MRP2 include tenofovir disoproxil fumarate and talinolol, among others [48,61,80,97]. …”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%